Methylation of the T-DNA in Agrobacterium tumefaciens and in several crown gall tumors. - Gelvin, S B (1983)
Methylation of the T-DNA in Agrobacterium tumefaciens and in four octopine-type (A6S/2, E9, 15955/1, 15955/01) and one nopaline-type (HT37#15) crown gall tumors was investigated using the isoschizomeric restriction endonucleases Msp I and Hpa II. T-DNA in the octopine-type Ti-plasmid pTiB6(806) was not methylated at the sequence 5'CCGG3' in Agrobacterium. With two possible exceptions, neither was the T-DNA of the nopaline-type Ti-plasmid pTiT37 methylated in the bacterium. In all tumor lines investigated, at least one copy of the T-DNA was not methylated. DNA methylation was not detected in the lines A6S/2, 15955/1, HT37#15, and the TL region of E9. DNA methylation of some copies of TR in the E9 tumor line, and possibly in the 15955/01 line, was detected. The methylation of some copies of TR in the E9 line may indicate that not all copies of TR are transcribed in this tumor.